Synthesising tannin-based coagulants for water and wastewater application: A review - Azreen, Ibrahim; Abu Zahrim, Yaser; Junidah, Lamaming (Elsevier Science, Ltd., 2021)
Coagulation-flocculation has been applied widely in water and wastewater treatment. Tannin, a natural watersoluble polyphenol that is present in most vegetable cells, has been widely accepted and applied as a plant-based coagulant. The application of a tannin-based coagulant in water and wastewater treatment around the world has shown successful removal of pollutants including turbidity, colourants, suspended solids, chemical oxygen demand, algae, and heavy metals. The level of effectiveness of tannins as a coagulant is associated with their chemical structure and the degree of tannin modification, which are linked to the plant source from which they are extracted. This review summarises the characteristics of tannin, extraction techniques applicable to tannin, as well as factors affecting tannin modification during the synthesis process. Developments and prospective of tannin-based coagulants as application in various types of water and wastewater treatment are also being reviewed.